EFEKTIVITAS PENGGUNAAN PASTA GIGI HERBAL EKSTRAK DAUN SIRIH DAN EKSTRAK SIWAK TERHADAP pH SALIVA - Syahdiana Waty; Sani Aspipa Harahap; Nurul Hidayah; Yetti Lusiani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
The degree of acidity or pH (potential of hydrogen) of saliva is an important factor that plays a role in dental caries, periodontal disorders and other diseases in the oral cavity. The mechanical action of brushing your teeth is the most basic action for cleaning your teeth and mouth. Brushing teeth is accompanied by the use of toothpaste which contains several elements including herbal ingredients, detergent, water, binders, sweeteners, therapeutic ingredients and anti-bacterial substances. The herbs contained in toothpaste can affect the pH of saliva as one of the factors causing dental caries. This research method is quasi experimental design. This study aims to determine the effectiveness of using herbal toothpaste with betel leaf extract and miswak extract on salivary pH. A sample of 38 respondents was divided into 2 groups, namely the betel leaf and siwak herbal toothpaste groups. Samples were asked to brush their teeth using toothpaste given 2 times a day for 7 days. The statistical test results of this study showed that there was a significant difference in saliva pH between before and after the intervention in the betel leaf herbal toothpaste group with a p value <0.05. There was also a significant difference in the miswak herbal toothpaste group between before and after intervention with a p value <0.05. The conclusion in this study is that the herbal toothpaste of betel leaves and miswak is effective in increasing saliva pH significantly with a p value <0.05. The use of herbal toothpaste from betel leaves and miswak is highly recommended for use in daily life because it is effective in increasing the pH of saliva so that it can reduce the factors that cause caries in Indonesian society.